Spread and Severity of Ash Dieback in Switzerland – Tree Characteristics and Landscape Features Explain Varying Mortality Probability - Klesse, Stefan; Abegg, Meinrad; Hopf, Sven E.; Gossner, Martin M.; Rigling, Andreas; Queloz, Valentin (Frontiers in Forests and Global Change, 2021)
Since the 1990s the invasive fungus Hymenoscyphus fraxineus has been threatening European ash (Fraxinus excelsior), a tree species with high ecological and economic importance. This pathogen is causing severe crown dieback, leading to high mortality rates across Europe and is present in Switzerland since 2008. In this study, we provide a comprehensive overview of the temporal evolution of crown damage and mortality rates in Switzerland over the 2009-2019 period. Harnessing the power of the annualized design of the Swiss national forest inventory, we show that annual mortality rates of ash increased significantly since the arrival of the fungus, with stronger effects in small trees (<26 cm DBH). Mortality modeling confirmed a size and growth-rate dependent mortality probability (MP). It also revealed that stands with higher humidity – either through higher mean annual precipitation or more humid soil conditions – showed also increased MP. Decreasing host abundance with increasing elevation was also associated with lower MP. Special ash surveys performed over the last ten years still show a large percentage of ash trees with very low defoliation. This gives hope to finding possible tolerant or resistant trees for (inter-)national breeding programs. In the mean-time our results reinforce previously published management guidelines to promote not only healthy big trees, but also healthy and fast-growing young trees in more open stands for future conservation of ash in Europe.